THE GLOSS OF POETRY - Jumanazarova Rayxon Jaloliddinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article analyzed the artistic criteria of the work of Nodira Ofak and Halima Ahmad, as well as specific poems in our literature. Their individual style, the system of images created by them, the interpretation of the world, the interpretation of the Motherland, the process of expressing in a specific style the person and the universe, the reality, the subtle human feelings in his soul. The poets ’ present-day Uzbek poetry commented on the complexity, contradictions, dishonesty in the human heart, justice, disgrace, and truthful, especially unique singing.